LATIHAN TRX (TOTAL BODY RESISTANCE EXERCISE) DAPAT MENINGKATKAN KECEPATAN RENANG 50 M GAYA KUPU-KUPU - Jannadine Uchaera; Maulidin Maulidin; Muhsan Muhsan (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2020)
The background of this research is the development of swimming clubs, especially in Indonesia, is also increasing, with the existence of PRSI as a center for swimming sports organizations, so that all provinces must have many clubs with outstanding athletes. In Indonesia, there have been many major championships so that many clubs have participated and shown their athletes to win. So that there is a very tight competition here. In NTB, swimming clubs have started to develop rapidly, with evidence that many championships are being held with many new clubs registering their athletes for each event. We can see this from the number of participants who took part in the existing championships and this development resulted in several NTB athletes who could compete at the national level. One of them, with a record time entered into the top 5 National, namely Nagata Exelian Yuva Harsono from Club Dragon Swimming Club Rebond in the 100 m style in the East Java Open Cup 2019 in Indonesia, the record time has entered in the top 5, namely 1.16.52 seconds . The same thing happened to NTB athletes with backstroke and freestyle specialists, namely Ricky Alexander and Haris Raynor. However, only butterfly style, no athlete has ever entered the top 10 of the National record. And this problem makes researchers want to offer an alternative solution in the form of Total Body Resistance Exercise (TRX) to athletes who are in KU II by providing an Exercise Program for 6 weeks